1994
DOI: 10.1111/j.1365-2672.1994.tb03449.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling growth and off‐flavours production of spoiled beer bacteria, Pectinatus frisingensis

Abstract: The genus Pectinatus includes strictly anaerobic Gram‐negative non‐spore‐forming mesophilic bacteria often referred to as beer‐spoilage bacteria. Pectinatus frisingensis was chosen as the reference strain. The organisms were grown in batch cultures under stringent anaerobic conditions in a synthetic medium and with pH regulation. Various glucose and lactate concentrations were used, and a low inoculum reproduced spoilage conditions in bottled beer. Propionate and acetate are the major compounds responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…Chromatographic Identification Pectinatus species are the only bacteria known to produce large quantities of propionic acid in beer, and hence gas chromatography has proved to be a useful tool for identification purposes Haikara et al, 1981b;Lee et al, 1978;Lee et al, 1980;Schisler et al, 1979;Membré and Tholozan, 1994;Foster and Beckler Andersen, 1999). The production of acetic acid in broth media and in beer further confirms the presence of Pectinatus (Foster and Beckler Andersen, 1999).…”
Section: Pectinatusmentioning
confidence: 62%
See 1 more Smart Citation
“…Chromatographic Identification Pectinatus species are the only bacteria known to produce large quantities of propionic acid in beer, and hence gas chromatography has proved to be a useful tool for identification purposes Haikara et al, 1981b;Lee et al, 1978;Lee et al, 1980;Schisler et al, 1979;Membré and Tholozan, 1994;Foster and Beckler Andersen, 1999). The production of acetic acid in broth media and in beer further confirms the presence of Pectinatus (Foster and Beckler Andersen, 1999).…”
Section: Pectinatusmentioning
confidence: 62%
“…A number of studies on Pectinatus growth in the culture medium as a function of temperature, pH and ethanol concentration have been performed (Tholozan et al, 1996;Tholozan et al, 1997;Chihib and Tholozan, 1999a;Chihib et al, 1999b) including modeling of growth and metabolite production (Membré and Tholozan, 1994;Watier et al, 1996b). In general, the parameters derive from those encountered in beer production, including rapid temperature changes in pasteurization and cooling before bottling.…”
Section: Physiological and Biochemical Properties Of Pectinatusmentioning
confidence: 99%
“…Pectinatus and Megasphaera proliferate in beer with an oxygen content of less than 0.3 mg/l, contamination is therefore a particular problem in large modern breweries (Back, 2005). The species P. frisingensis tolerates more oxygen than P. cerevisiiphilus -a laboratory study of both species demonstrated their ability to grow in beers with a content of dissolved oxy- Hlavním produktem metabolismu bakterií Pectinatus je propionát v množství až 100 mmol/l, dále acetát, acetoin, sirovodík, methylmerkaptan a dimethylsulfid a stopová množství butyrátu (Membré a Tholozan, 1994;Schleifer et al, 1990). Megasphaera produkuje butyrát jako hlavní produkt, dále pak izobutyrát, propionát, valerát, izovalerát, kaproát a sirovodík (Chelack a Ingledew, 1987).…”
Section: ■ ■ 3 the Ability Of Strictly Anaerobic Bacteria To Spoil Beerunclassified
“…Ethanol není těmito mikroorganismy využíván ani produkován [9]. Hlavním produktem metabolismu bakterií Pectinatus je propionát v množství až 100 mmol/l [16], dále acetát, acetoin, sirovodík, methylmerkaptan a dimethylsulfid a stopová množství butyrátu [6].…”
Section: Pectinatusunclassified
“…They neither utilize nor produce ethanol [9]. The main metabolic product of Pectinatus bacteria is propionate in amounts of up to 100 mmol/l [16], and also acetate, acetoin, hydrogen sulphate, methylmercaptan and dimethylsulfide, and trace amounts of butyrate [6].…”
Section: Pectinatusmentioning
confidence: 99%